Tetrahydroxystilbene Glucoside Attenuates Neuroinflammation through the Inhibition of Microglia Activation. (14th November 2013) - Zhang, Feng; Wang, Yan-Ying; Yang, Jun; Lu, Yuan-Fu; Liu, Jie; Shi, Jing-Shan
Abstract : Neuroinflammation is closely implicated in the pathogenesis of neurological diseases. The hallmark of neuroinflammation is the microglia activation. Upon activation, microglia are capable of producing various proinflammatory factors and the accumulation of these factors contribute to the neuronal damage. Therefore, inhibition of microglia-mediated neuroinflammation might hold potential therapy for neurological disorders. 2, 3, 5, 4′-Tetrahydroxystilbene-2-O- β -D-glucoside (TSG), an active component extracted from Polygonum multiflorum, is reported to be beneficial for human health with a great number of pharmacological properties including antioxidant, free radical-scavenging, anti-inflammation, antilipemia, and cardioprotective effects. Recently, TSG-mediated neuroprotective effects have been well demonstrated. However, the neuroprotective actions of TSG on microglia-induced neuroinflammation are not known. In the present study, microglia BV2 cell lines were applied to investigate the anti-neuroinflammatory effects of TSG. Results showed that TSG reduced LPS-induced microglia-derived release of proinflammatory factors such as TNF α, IL-1 β, and NO. Moreover, TSG attenuated LPS-induced NADPH oxidase activation and subsequent reactive oxygen species (ROS) production. Further studies indicated that TSG inhibited LPS-induced NF- κ B signaling pathway activation. Together, TSG exerted neuroprotection against microglia-mediated neuroinflammation, suggesting that TSG might present a promising benefit for neurological disorders treatment.